In so many words - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Glossary of biotechnology for food and agriculture A revised and augmented edition of the Glossary of biotechnology and genetic engineering, FAO, 2001. 324 pp. ISBN 9251046832 US$ 16 Euro 15.55